Phaseolus vulgaris extract affects glycometabolic and appetite control in healthy human subjects - Spadafranca, Angela; Rinelli, Samuele; Riva, Antonella; Morazzoni, Paolo; Magni, Paolo; Bertoli, Simona; Battezzati, Alberto (British journal of nutrition, 2013)
Extracts of Phaseolus vulgaris (beans) are known to reduce glycaemia and food intake in rodents and humans. The present study evaluated the effects of a new, standardised and purified P. vulgaris extract (PVE), when employed as a supplement in a mixed balanced meal (60 % carbohydrates, 25 % lipids and 15 % protein), on glycometabolic and appetite control. To this end, a randomised, double-blind, placebo-controlled study was performed in twelve volunteers. Plasma glucose, insulin, C-peptide, ghrelin and satiety sensation ratings were assessed at baseline and during 3 h after meal consumption associated with PVE (100 mg) or placebo. Compared with placebo, PVE consumption resulted in lower increments in glucose (+15·4 (sem 5·4) v. 26·1 (sem 7·3) %, P= 0·04 at 30 min), insulin (+981 (sem 115) v. 1325 (sem 240) %, P= 0·04 between 45 and 120 min) and C-peptide (+350 (sem 27) v. 439 (sem 30) %, P= 0·04 between 30 and 90 min). In the first 2 h, plasma ghrelin decreased similarly in both groups but did not rebound as in placebo thereafter (P= 0·04). Correspondingly, satiety sensation in the third hour was significantly reduced in the placebo but not in the PVE condition. PVE induced a lower desire to eat than placebo (P= 0·02) over the 3 h. In conclusion, PVE supplementation reduced postprandial glucose, insulin and C-peptide excursions, suppressed ghrelin secretion and affected satiety sensations, inducing a lower desire to eat. These results support that further studies are needed to prove the concept of employing PVE as a supplement in mixed balanced meals in obese, glucose-intolerant and diabetic subjects.